ANALYSIS OF THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES (SAK EMKM) IN BENGKALIS SUBDISTRICT - Sasmita, Ayu; Asiam, Siti (MBISKU: Jurnal Manajemen Bisnis dan Keuangan, 2025)
Indonesia as a developing country prioritizes its economic growth because of the many jobs created, the Micro, Small, and Medium Enterprises (MSMEs) sector is important for the Indonesian economy. Along with the progress of MSMEs in compiling financial reports, Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) have been introduced. SAK EMKM, which is regulated by the Indonesian Institute of Accountants (IAI) and has been effectively enforced since January 1, 2018. This is intended to enable MSMEs to prepare and audit their own financial reports. Although simple, the standard does not significantly change the principles that are generally applied today. This study focuses on 1) how the implementation of SAK EMKM is at MSME Ilham Market, and 2) what are the obstacles in the implementation of SAK at MSME Ilham Market. The purpose of this study is to determine the implementation of SAK EMKM at MSME Ilham Market and to determine the obstacles in the implementation of SAK EMKM at MSME Ilham Market. The research method uses a qualitative approach with field studies through observation, interviews, and documentation, as well as data analysis with data reduction, data presentation, and verification. Data validity is obtained through source triangulation. The results of the study indicate that the financial reports that have been carried out by Toko Ilham Market have not been implemented in accordance with the provisions of the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The obstacles experienced by Toko Ilham Market in implementing the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) include the lack of human resources who have knowledge of SAK EMKM and the absence of socialization and training of SAK EMKM in MSMEs..